Incident Occurrence Modeling during Hurricane Evacuation Events: The Case of Alabama's I-65 Corridor. (7th October 2013) - Fonseca, Daniel J.; Lou, Yingyan; Moynihan, Gary P.; Gurupackiam, Saravanan
Abstract : Contraflow on major evacuation routes is one scheme that has been adopted in many Gulf and eastern coastal states for hurricane evacuation. The idea is to reverse one direction of the roadway in order to accommodate the often substantially increased travel demand moving away from the impact area. Efficient planning and operation is critical to a successful contraflow implementation. Alabama has an approximately 140-mile contraflow segment on I-65 between exit 31 and exit 167 and has carried out contraflow operations several times in past hurricane evacuations. The timing for the deployment of equipment and personnel and the initiation and termination of actual contraflow affects the effectiveness, safety, and cost of the operation. Researchers from the University of Alabama were tasked with the design of a decision support system for contraflow evacuation planning. The conceived decision support system consists of three main modules: the demand module, the network optimization module, and the incident and characterization module. This paper focuses on the design of the traffic incident generation and characterization module of the planned decision support system.